37. Geology and Exploitation of Uranium Deposits in the Lisbon Valley - Hiram B. Woon (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Uranium ore deposits in the Lisbon Valley area are in an arcuate belt, 15 miles long by one-half-mile wide, on the southwest flank of the Lisbon Valley anticline. They range in size from 500 to 1,500,000 tons and by mid-1965 had yielded 6,147,000 tons containing 48,530,000 pounds of U3O8. Ore bodies average 6 feet thick, are tabular, amoeba-shaped masses, concordant to the bedding, and are in the thickest, lowest sandstone unit of the Moss Back Member of the Chinle Formation of Triassic age. The host rock is predominantly a fluviatile, calcareous, fine-grained to conglomeratic sandstone. Uraninite, the principal ore mineral, fills the pores in the sandstone and partly replaces sand grains and fossil wood fragments. During Late Permian and Early Triassic time pre-Chinle Formations were arched to form the ancestral Permian anticline. Moss Back streams truncated Moenkopi and Cutler beds which capped the ancestral anticline and then covered it with fluviatile elastics, which were subsequently covered by thousands of feet of Triassic, Jurassic, and Cretaceous sediments. Uranium, probably derived from the Chinle Formation by diagenetic processes, was transported in connate ground waters, was moved by compaction or hydrostatic forces, and was deposited under reducing conditions. Uranium was emplaced around the crest of the ancestral anticline, prior to the Laramide orogeny. During the orogeny, the Tertiary-Lisbon valley anticline was super induced on the Permian anticline and, penecontemporaneous with uplift, was faulted parallel to its longitudinal axis. The Big Indian ore belt on the southwest flank footwall block was elevated to approximately its present position, and the northeast flank hanging wall block was elevated only slightly. An extension of the Big Indian ore belt around the northeast flank of the ancestral Permian anticline may exist in the Moss Back sandstone in the downthrown block northeast of the Lisbon Valley fault.